Hydrothermal liquefaction of spent coffee grounds followed by biocatalytic upgradation to produce biofuel: a circular economy approach. Issue 6 (24th May 2022) - Muller, Louis Christiaan; Pearson, Jaco; Louw, Jaco; Marx, Sanette; Kumar Karmee, Sanjib
Abstract: Hydrothermal liquefaction (HTL) of wet spent coffee grounds was performed in a batch reactor for bioenergy production. The effects of spent coffee grounds to water ratio, temperature and reactor volume occupation on product yield were investigated. A maximum 19.1 wt% bio-oil yield with HHV of 38.5 MJ/kg was obtained from wet spent coffee grounds. Subsequently, the bio-oil synthesized via hydrothermal liquefaction was upgraded biocatalytically to bring down the acid value and to convert the bio-oil into a higher quality liquid biofuel. During this process the fatty acids present in the bio-oil were converted into fatty acid methyl esters (biodiesel) using lipase. Novozyme-435 converted ∼ 85% of fatty acids in the bio-oil into fatty acid methyl esters at 35 °C after 14 h, as determined by 1 H NMR. In addition, FTIR analysis confirmed the presence of fatty acid esters in the product. The acid number of the bio-oil decreased significantly after the enzymatic reaction. The results shows that lipase is an effective biocatalyst for crude bio-oil upgradation.